How climate change and natural hazard risk affect the Auckland property market : a thesis presented in complete fulfillment of the requirements for the degree of Master of Business Studies (MBS) in Finance at Massey University, Auckland Campus, New Zealand - Islam, Md Tahminul (Massey University, 2025)
This thesis examines the effects of natural hazard and climate change risks on the Auckland property market. The study incorporates a quantitative comparative research design, and integrates diverse data sources, including Auckland Council, Barfoot & Thompson, Ministry of Education, Reserve Bank of New Zealand and so on for investigation. The key variables considered in this study are natural hazard and climate change risks, school equity, socioeconomic deprivation, distance to the central business district, proximity to tertiary institutes, Official Cash Rate, GDP per capita, Inflation and Price to Rent ratio. This study also examines the impact of Natural Hazard risks on Property Sales prices and rental prices. Analytical techniques comprise descriptive statistics, stationarity tests, multicollinearity test, regression modelling and additional analyses to comprehensively analyze the impacts of climate related risks while controlling locational, social, and economic factors. The outcomes indicate that properties that are in areas with higher environmental hazard risks, have lower property sale prices and consequently, lower price to rent ratio. However, the rental prices remain stable and don’t reflect significant deviations due to climate risks. This suggests a market adjustment to anticipated environmental vulnerability and buyer’s preference to factor climate risks in the long-term buying decision. Whereas rental demands are short term and reflect immediate needs and thus don’t deviate due to climate risks. These also indicate tangible implications for investment decision-making, property valuation, and urban planning strategies. This study contributes to the expanding field of environmental economics and property market research by linking the environmental risks to the property market outcomes. The outcomes suggest the investors, urban planners, policymakers, and other related stakeholders to integrate climate risks into property market assessments, sustainable urban planning and development. This thesis also underlines the importance of necessity of adopting evidence-based strategies to mitigate the financial and social impacts of environmental hazards in urban areas, positioning Auckland’s housing market as a case study for broader implications in similarly exposed metropolitan contexts.
Keywords: 350208 Investment and risk management